Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/2016gl070742
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude‐based discrimination of man‐made seismic events from naturally occurring earthquakes in Utah, USA

Abstract: We investigate using the difference between local (ML) and coda/duration (MC) magnitude to discriminate man‐made seismic events from naturally occurring tectonic earthquakes in and around Utah. For 6846 well‐located earthquakes in the Utah region, we find that ML‐MC is on average 0.44 magnitude units smaller for mining‐induced seismicity (MIS) than for tectonic seismicity (TS). Our interpretation of this observation is that MIS occurs within near‐surface low‐velocity layers that act as a waveguide and preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Details of the procedures used by UUSS to calculate magnitudes are available in Pechmann et al (2006) for M C and in Pechmann et al (2007) for M L . The two magnitude scales are designed to be seamless, and for earthquakes in the Utah region that occur deeper than 3-4 km, the average M L -M C is near zero (Koper et al, 2016). Breckenridge et al (2003).…”
Section: Earthquake Locations and Magnitudesmentioning
confidence: 99%
“…Details of the procedures used by UUSS to calculate magnitudes are available in Pechmann et al (2006) for M C and in Pechmann et al (2007) for M L . The two magnitude scales are designed to be seamless, and for earthquakes in the Utah region that occur deeper than 3-4 km, the average M L -M C is near zero (Koper et al, 2016). Breckenridge et al (2003).…”
Section: Earthquake Locations and Magnitudesmentioning
confidence: 99%
“…A major, obvious difference concerns their shallow hypocentral depth, which may affect other source parameters and signal characterization. For example, Koper et al [] found anomalous deviations among local and coda/duration magnitude for mining‐induced seismicity, with respect to tectonic events and used this parameter to discriminate induced seismicity; this anomaly was interpreted as a consequence of the shallow depth of mining‐induced seismicity, located within near‐surface low‐velocity layers acting as a waveguide for trapped waves, thus increasing the signal duration at the cost of a lower peak amplitude, as sometimes observed at volcanoes. Even a low‐aftershock productivity evidenced, e.g., by Dahm et al [] for an induced earthquake in Germany, in comparison to tectonic earthquake of similar magnitude in the same region, could be finally linked to the shallow source location within different geological units.…”
Section: Challenges In Discriminating Induced/triggered From Natural mentioning
confidence: 99%
“…One factor that interferes with the classification is an artificial explosion. Artificial explosions, e.g., quarry blasts, explosive bomb tests, and underground nuclear tests, accompany seismic tremors, and the surface oscillations are similar to earthquakes [ 1 ].…”
Section: Introductionmentioning
confidence: 99%